If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = 38x + 17 Reorder the terms: 13 + -7x = 17 + 38x Solving 13 + -7x = 17 + 38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38x' to each side of the equation. 13 + -7x + -38x = 17 + 38x + -38x Combine like terms: -7x + -38x = -45x 13 + -45x = 17 + 38x + -38x Combine like terms: 38x + -38x = 0 13 + -45x = 17 + 0 13 + -45x = 17 Add '-13' to each side of the equation. 13 + -13 + -45x = 17 + -13 Combine like terms: 13 + -13 = 0 0 + -45x = 17 + -13 -45x = 17 + -13 Combine like terms: 17 + -13 = 4 -45x = 4 Divide each side by '-45'. x = -0.08888888889 Simplifying x = -0.08888888889
| x=2.26*y | | -3f^2+4f+-3+8f^2+7f+1= | | 2x+30=-100 | | n^2-7n+2=0 | | 110-4x=3x+24 | | -7(x)=2x+8 | | 3(5x-2)+4x=9x+6-2 | | 12x-6=24 | | 5y-21=3y+3 | | 11x+12=8x-32 | | 14=9x-2 | | (x+10)(x^2+9x-8)= | | -63=-9d | | 6x/7=35 | | 3x+21=14x-84 | | 2x+29=9x-14 | | R/-6=-1 | | X^6-27=0 | | (x^2-6x+8)(3x+24)=0 | | 1/(1.10x-1.1)=2.90 | | 3(2x+12)=-15 | | 12x-16=12x-9-6 | | x^2=x+44 | | 6+64=70 | | -3x+6(x-4)=9 | | -1-5x=5x+7 | | 7=6x+19 | | 3f^2+4f-3+8f^2+7f+1= | | -5x+3(x+5)=1 | | 40+40x=70-45x | | 3-1/x | | 2t+1+4t-5t= |